A New Witness to the Chronicle of John of Nikiu: EMML 7919 - Brown, Jeremy R.; Elagina, Daria (Aethiopica, 2018)
This article introduces a new witness to the Chronicle of John of Nikiu (EMML 7919). It analyses the text of this witness alongside the four previously known Ethiopic manuscripts of this work. The article considers the current state of research on the Chronicle of John of Nikiu, including an examination of the textual witnesses, the language of the original composition, and the biographical and historical information of the chronicler. The textual analysis of EMML 7919 demonstrates a strong relation with the text attested in ANL Conti Rossini 27, which suggests that EMML 7919 is highly valuable for the reconstruction of the Ethiopic version of the Chronicle of John of Nikiu. Finally, there is a catalogue entry for EMML 7919, which details the textual and codicological features of the manuscript.